Exploring the impact of art-based interventions on the mental health of domestic violence survivors: a comprehensive bibliometric analysis (2000-2023) - Liu, Xingcen; Kamal Sabran, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Arts-based interventions are gaining recognition for their significant impact on mental health, particularly for domestic violence survivors. This bibliometric analysis (2000-2023) reviews 70 studies, with 16 from Web of Science (WoS) and 54 from Scopus, to assess the effects of arts interventions on this population. Utilizing RStudio 4.2.1 and biblioshiny in bibliometrix, we identified a steady increase in Scopus publications and minor fluctuations in WoS. "Art therapy" was the most common keyword, with the International Journal of Art Therapy and Art in Psychotherapy receiving substantial attention. J. Bird emerged as the most influential author in Scopus, while WoS showed no prominent authors with all authors having a relevance score of 1. The United States led in research output, driving advancements in the field. The growing number of publications highlights the importance of arts interventions. Future research should integrate art-based interventions with other therapies, conduct rigorous empirical studies with long-term follow-ups, and develop culturally adaptive approaches to enhance their global applicability and effectiveness for domestic violence survivors.